Goji Berry and Whey Protein Concentrate Enriched Rice Extrudates - Physical Properties and Accessibility of Bioactives - Thomas Ménabréaz; Mathias Dorsaz; Dimitri Bocquel; Isabelle Udrisard; Agnieszka Kosinska-Cagnazzo; Wilfried Andlauer (Polish Journal of Food and Nutrition Sciences)
Extrudates are gaining popularity as convenient ready-to-eat products such as snacks or breakfast cereals. The nutritional limitation of extruded products is their low content of proteins, fibres, and phytochemicals. The challenge lies in increasing the nutritional value of extruded products while maintaining the quality of expansion. Goji berries are rich in bioactive compounds, such as polysaccharides, phenolic compounds, carotenoids, and an analogue of vitamin C. In the present study, rice flour-based extruded products were enriched with goji berries and whey protein concentrate. The varying addition of goji berries and whey protein concentrate affected expansion ratio, colour, and texture parameters of extrudates. The content and bioaccessibility of goji bioactives, i.e. 2- O -β-D-glucopyranosyl-L-ascorbic acid (2-β-gAA) and the dominant phenolic compound – rutin, were evaluated for two extrudates with the highest addition of goji and whey protein concentrate. The extrusion process significantly reduced the content of 2-β-gAA both in formulations with and without whey protein concentrate by approximately 15%. The bioaccessibility of 2-β-gAA was negatively affected by the extrusion process, but not that of rutin. The addition of whey protein concentrate at a level of 7% had no significant effect on the bioaccessibility of neither 2-β-gAA nor rutin.